2005
DOI: 10.1021/es051236b
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer Method to Determine Rate Constants for the Reaction of Carbonate Radical with Organic Compounds

Abstract: Carbonate radical (CO3*-) is a powerful oxidant that is present in sunlit surface waters and in waters treated by advanced oxidation processes. The production of CO3*- in aqueous solution through oxidation of carbonate anion by excited triplet states of aromatic ketones was investigated in this study to provide new methods for the determination of rate constants and to explore a possible photoinduced pathway of CO3*- formation in the aquatic environment. Rate constants for triplet quenching by carbonate anion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
334
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(348 citation statements)
references
References 47 publications
(81 reference statements)
2
334
0
2
Order By: Relevance
“…Chemical transformation not involving light, gas partitioning and sedimentation could be excluded (the latter because CBZ is polar and rather hydrophilic), 50 while biotransformation seems little likely for CBZ. 2,51 With data relevant to the epilimnion of Lake Greifensee (5 m depth, 0.1 mM nitrate, 3.5 mg C L −1 DOC, 2 mM bicarbonate, 10 µM carbonate 14,52 ) and Table 1 . This value is very near the field rate constant of CBZ attenuation after exclusion of the outflow, and suggests that photochemistry could play a role in the loss of CBZ in Lake Greifensee epilimnion.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical transformation not involving light, gas partitioning and sedimentation could be excluded (the latter because CBZ is polar and rather hydrophilic), 50 while biotransformation seems little likely for CBZ. 2,51 With data relevant to the epilimnion of Lake Greifensee (5 m depth, 0.1 mM nitrate, 3.5 mg C L −1 DOC, 2 mM bicarbonate, 10 µM carbonate 14,52 ) and Table 1 . This value is very near the field rate constant of CBZ attenuation after exclusion of the outflow, and suggests that photochemistry could play a role in the loss of CBZ in Lake Greifensee epilimnion.…”
Section: Resultsmentioning
confidence: 99%
“…The implications of the presence of such light-absorbing organics and the possible photochemical reactions are not yet well understood in the sea surface microlayer. But clearly, the presence of such photoactive compounds at the air/sea interfaces could give rise to photosensitized processes (Becker et al, 1995;Canonica et al, 2006Canonica et al, , 2000Canonica et al, , 2005Das et al, 1981;Ivanov et al, 2005;Lathioor and Leigh, 2001;Lathioor et al, 1999;Leigh et al, 1996) which may also affect chemistry in the marine boundary layer (MBL) (Reeser et al, 2008). Previously, we showed that chlorophyll may be a photochemical source of halogenated radicals or the driving force for ozone deposition at low wind speed (Clifford et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The hydroxyl radical is also formed by irradiation of CDOM, the latter through pathways that are not yet completely elucidated (Page et al, 2011;Glover and Rosario-Ortiz, 2013;Mostafa et al, 2014) and that could also involve iron-based species in Fenton/photoFenton processes. The radical CO 3 −• is formed upon oxidation of carbonate and bicarbonate by • OH (reactions 3, 4) and, to a lesser extent, upon carbonate oxidation by 3 CDOM* (Canonica et al, 2005). Singlet oxygen and 3 CDOM* are produced by CDOM irradiation according to reactions (6, 7, 8) (Coelho et al, 2011;Mostafa and Rosario-Ortiz, 2013;Marchisio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because CDOM is an important • OH source, but DOM is by far its main sink, the • OH levels can be negatively related with DOC. An even stronger negative relationship is often observed between DOC and CO 3 −• , because DOM both scavenges CO 3 −• and inhibits its formation by consuming • OH (Canonica et al, 2005;Vione et al, 2014). In contrast, • OH and CO 3 −• often positively correlate with nitrate and nitrite, and CO 3 −• with inorganic carbon species as well .…”
Section: Introductionmentioning
confidence: 99%